Pengaruh Struktur Modal, Kinerja Keuangan dan Keputusan Investasi Terhadap Nilai Perusahaan - Gamas Aditya, Muhamad; Angelica Cindiyasari , Shiwi (DINASTI RESEARCH, 2024)
This study aims to evaluate the impact of capital structure, financial performance, and investment decisions on firm value in consumer goods manufacturing companies in 2023. Using a sample of 30 companies selected through purposive sampling, the research employs classical assumption testing and multiple linear regression analysis using SPSS to assess the relationships among the variables. The findings indicate that financial performance and investment decisions have a positive and significant impact on firm value, while capital structure shows no significant effect. The F-test results confirm that the combination of these factors collectively influences firm value. Additionally, the coefficient of determination shows that 85.5% of the variation in firm value can be explained by these independent variables, with the remaining 14.5% influenced by other factors. This research contributes to the literature on corporate finance by providing insights into the dynamics of capital structure, financial performance, and investment decisions, all within the context of the consumer goods manufacturing sector in Indonesia.